Efficiency of coco peat in adsorbing Cd(II) evaluation using batch tests - Pingul, Sheila Mae Batan (2010)
The efficiency of coco peat in adsorbing cadmium (II) ions from aqueous solution was evaluated at different initial solution pH, sorbent-solution contact time, initial ion concentration in the solution, and sorbent particle size. Batch experiment were conducted at laboratory scale, varying the initial solution pH from 0 to 8, sorbent-solution contact time from2 minutes to 6 hours, initial cadmium (II) ion concentration from 20 to 300 ppm, and coco peat particle size from <0.42 to 2.00 mm in diameter. Results show that maximum adsorption of 99.49% was achieved at pH 7; reaction reached equilibrium after 2 hours; and percent removal was inversely proportional to both initial ion concentration and biomass particle size. Maximum adsorption capacity of coco peat for cadmium (II) was 28.57 mg/g. The equilibrium behavior of the adsorption process was better described by Freundlich that Langmuir isotherm. The rate of reaction was rapid, and it follows pseudo-second order kinetics.
"October 2010"
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Adsorption; Coir